2019
DOI: 10.1371/journal.pone.0211345
|View full text |Cite
|
Sign up to set email alerts
|

Job preferences for healthcare administration students in China: A discrete choice experiment

Abstract: BackgroundThere is a deficiency of healthcare administrators in China as compared with other countries; furthermore, the distribution is unequal. To inform an effective policy intervention, it is crucial to understand healthcare administration students’ career decision-making. This study aims to investigate the undergraduate students’ stated preferences when choosing a job.MethodsA discrete choice experiment (DCE) was conducted among a population-based multistage sample of 668 final year undergraduate healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 48 publications
0
25
5
Order By: Relevance
“…Many included studies (39%) did not provide a definition of rural. Many (39%) also defined ‘rural’ based on non-facility aspects such as level of socioeconomic deprivation [ 32 , 51 , 53 , 57 , 62 , 70 , 86 , 90 , 91 ], being located outside of metropolitan areas [ 26 29 , 48 , 82 ], population size [ 42 , 65 ], administrative unit definitions [ 36 , 77 , 84 ], and geographical access [ 50 , 52 , 56 , 58 , 83 ]. Some (14%) studies defined rural as working in primary care or community-level facilities or smaller hospitals [ 31 , 47 , 49 , 61 , 63 , 64 , 67 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many included studies (39%) did not provide a definition of rural. Many (39%) also defined ‘rural’ based on non-facility aspects such as level of socioeconomic deprivation [ 32 , 51 , 53 , 57 , 62 , 70 , 86 , 90 , 91 ], being located outside of metropolitan areas [ 26 29 , 48 , 82 ], population size [ 42 , 65 ], administrative unit definitions [ 36 , 77 , 84 ], and geographical access [ 50 , 52 , 56 , 58 , 83 ]. Some (14%) studies defined rural as working in primary care or community-level facilities or smaller hospitals [ 31 , 47 , 49 , 61 , 63 , 64 , 67 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…A broad range of educational factors were associated with rural work, especially related to rural background. Both preference and actual work in rural locations were associated with having resided in rural areas during the school-age period, having graduated from a rurally located high school, or being a native of a particular (1) had no definition of rural or no description of the place characteristics where the study was done and this was not cross-referenced to an earlier study by the authors [66, 68, 69, 74-76, 78, 81, 92], or; (2) relied on respondents' own definition of rural [33-35, 37, 39, 40, 43-45, 54, 55, 73, 79, 80, 88, 89, 93, 94, 98] Facility-related Type of health facility 9 1 0 10 (14.1) Township-village health center [47,95], county or township hospital [61], community or primary or additional primary health centers, secondary hospital [67], community hospital [31,49], government rural health unit [63,64] Non-facility related Population size 2 0 0 2 (2.8) City/municipality with less than 100,000 population [65], district with < 25,000 population [42] Non-metropolitan 6 0 0 6 (8.5) Area outside the country capital and/or large city [26-29, 48, 82] Administrative unit 3 0 0 3 (4.2) Any area of county, town or village [36]; rural or farther rural [84]; township or rural county [77] One of the most rural regions in a country 2 4 4 10 (14.1) Rural relative to other areas in the country, such as: Kampong Chhnang in Cambodia, Guangxi in China [32]; Bac Giang, Lao Cai and Thai Binh in Vietnam [32,70]; Chattisgarh and Odisha in India [53,57,86,91], East Nusa Tenggara in Indonesia and Zamboanga in the Philippines [32,51,53,57,62,70,86,90] Access and/or topography 2 3 0 5 (7.0) Limited c...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used qualitative research as well as a literature review to select attributes to be included in the DCE. Initially, ten attributes commonly adopted and suitable for the Chinese health system were identified through our previous research experience [13] and a literature review [14][15][16] , which were monthly income, Bianzhi, location, housing, children's education, working environment, career promotion, workload, management style, training and career development opportunity. An in-depth interview was then conducted with 7 SMHCM PhD students from Fudan university and Shandong University, which suggested that the attribute of management style and workload could be removed.…”
Section: Selection Of Attributes For the Choice Experimentsmentioning
confidence: 99%